Literature Review: Internalization of Noble Moral Values in Islamic Religious Education Learning in Secondary Schools in the Era of Globalization - Qurrota A’yun, Afifah; Khairani, Elvi; Resti Aprilia, Nabilla; Aulia Rahmi, Nurul; Jannah, Raudatul (Universitas Islam Lamongan, 2026)
This literature review aims to map internalization strategies for noble moral values in Islamic Religious Education (IRE) learning; identify supporting and inhibiting factors; analyze conceptual gaps in existing literature to formulate a more comprehensive synthesized framework. Data were collected through library research with content analysis of scientific journals and relevant academic documents. Findings indicate that noble moral value internalization strategies include teacher role-modeling, habituation of religious activities, value integration into the curriculum, and school-family collaboration. Supporting factors include teacher competence, religious school culture, adequate facilities, and student motivation; inhibiting factors include globalization influences, uncontrolled digital media, and low parental involvement. This review contributes an integrated conceptual framework to guide future empirical research and IRE curriculum development.